INTEGRASI FUZZY LOGIC DAN MINIMAL REPAIR DALAM PENJADWALAN PERAWATAN MESIN UNTUK MENGOPTIMALKAN LIFETIME MESIN PRODUKSI - , Priyo Widodo, Andi Rahadiyan Wijaya., S.T., M.Sc., Lic., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Production machines are one of the main assets of the company. The machines may not be the perfect level of reliability at all times. Over time, a machine will have breakdown and the breakdown may occur is uncertain. Uncertainty breakdown machine would cause losses greater than the scheduled maintenance. Therefore, it is necessary to scheduling machine maintenance. The machine maintenance will restore and or maintain the condition of the machine at particular state. It depends on the quality of machine maintenance. The better rate of quality maintenance as a result of the maintenance machine, the machine lifetime production machine will be more optimal. The concept of fuzzy logic and minimal repair is an approach that can accommodate uncertainty and the quality of maintenance. In this research, the two concepts will be integrated to scheduling maintenance of production machine. Moreover, it will be built also interface for user interface to facilitate the use of this software. This research uses a case study of PT Holcim Indonesia, Cilacap plant and focus on finish mill area, especially Ball Mill machine. This is because these areas have the availability and MTBF lower than other area that is 92.27% and 21.02 hours. This means that in these areas often have breakdown. When integrate, minimal repair is used as one of the inputs in the fuzzy model in addition to the reliability and cost. The results of this research found the period of machine maintenance 5 times in 1 year with savings of almost 11,78% of the cost of maintenance has been done now. Scheduling maintenance of the machine is the first for maintain Motor, and the second for Diaphragm, third for Temperature Bearing, Bolt Liner, Bolt Man Hole, and Vibration Bearing, fourth for, Mill Chamber and Ball Mill and last for Inlet Ball Mill. Keywords: Scheduling Machine Maintenance, Breakdown, Lifetime Optimization, Fuzzy Logic, Minimal Repair